Leveraging development programs—Livestock research - Baltenweck, Isabelle; Banerjee, Rupsha R.; Omondi, Immaculate A. (Elsevier, 2019)
Livestock systems and value chains, while offering important opportunities for enhanced livelihoods, face various challenges. The agenda for development effort is to address these challenges. Livestock research, on the other hand, plays a key role in generating new knowledge, evidence and technologies. In this paper, we discuss how livestock research and development interact. We present an impact pathway with two main channels through which research contributes to development outcomes, first through localized applied research and secondly through the creation of International Public Goods (IPGs). However, it is also important to also recognize how development efforts influence the research agenda.